Tuning the reactivity and efficiency of copper catalysts for atom transfer radical polymerization by synthetic modification of tris(2-methylpyridyl)amine. (16th October 2017) - Carmo dos Santos, Nadia Alessandra; Lorandi, Francesca; Badetti, Elena; Wurst, Klaus; Isse, Abdirisak Ahmed; Gennaro, Armando; Licini, Giulia; Zonta, Cristiano
Abstract: Copper complexes bearing ligands based on tris(2-methylpyridyl)amine (TPMA) are leading catalysts in atom transfer radical polymerization (ATRP). In recent years, the TPMA structure has been finely modified to enhance the catalytic activity of the corresponding Cu complex. In this study, we report the synthesis of eight novel copper TPMA complexes, and the evaluation of the catalytic activity for electrochemically mediated ATRP in both organic and aqueous media. The TPMA skeleton was modified by inserting differently m -functionalised phenyl substituents. Complete characterizations and electrochemical investigations were performed to define the structural and redox properties of the new complexes and compare them to the archetype Cu/TPMA. Well-controlled polymerizations of some hydrophobic, hydrophilic and acidic monomers are presented, with conversions > 80%, low dispersity and predetermined molecular weights, thus confirming that these compounds are suitable ATRP catalysts for different systems. Graphical abstract: Highlights: TPMA modified with functionalised phenyl groups as ligand for Cu-mediated e ATRP. Crystallographic and electrochemical characterization of 8 new Cu complexes. Tuning the control over e ATRP of MMA with different ligands. Good performances of a new Cu catalyst in e ATRP of hydrophilic and acid monomers.